Medically refractory Mondor’s disease of the penis - Hugo Rivera-Astorga; María P. Vázquez-Tabares; Paulina L. León-López; Ángel Gurrola-Ortega; Jorge Jaspersen-Gastelum; José F. Virgen-Gutiérrez; Eloy Rico-Frontana; César A. Rivera-Colín (Revista Médica del Hospital General de México)
The case involves a 24-year-old male diagnosed with Mondor’s disease, with a duration of 3 months and resistance to anti-inflammatory pharmacological treatment. The decision is made to pursue surgical management through the resection of the dorsal vein of the penis. Mondor’s disease typically exhibits self-limiting characteristics. Surgical intervention is considered when the patient proves resistant to conservative treatment after 8 weeks. It is essential to opt for a minimally invasive surgical approach to mitigate complications such as fibrosis or erectile pain, thereby enhancing the patient’s quality of life.